CAMPUR KODE BAHASA JEPANG DI MEDIA SOSIAL MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG TINGKAT II FKIP UNIVERSITAS RIAU - Roni Fajri; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is aimed to analyze code mixing which spoken directly by japanese students in social media. Methode in research qualitative and descriptive methode that using literature study researc instrument. The object of this research is the expressing of code mixing in social media such as; facebook, twitter, instagram, line, and whatsapp. In this research found code mixing in words, phrase, baster, word repeatation, idiom, and clause. So, in conclusions the students disposed japanese word inserting on their social media status, due to word code mixing is easier and simple used in status. The factor that influence code mixing occurs in the group of japanese education students in FKIP Universitas Riau are the partner that decreasing humor sense and just prestigious.Key Words : Mixing Code, Social Media, Japanese Language